Desenvolvimento de um equipamento para avaliação funcional de joelho - Meereis, Estele Caroline Welter (2013)
The knee is considered one of the most complex joints in the human body, and the main muscles responsible for the dynamic stabilization of the knee are the flexor and the extensor muscles. The evaluation of the muscle strength enables professionals to monitor the effectiveness of therapeutic interventions during rehabilitation and the efficiency of training in sports, as well as, detecting asymmetries of strength. One of the methods used for carrying out such evaluation is the dynamometer, which can evaluate the torque produced across the breadth of the isometric or isokinetic movement forms. However, such equipment is expensive and little accessible to the majority of professionals and researchers. Given this, the present work proposes the development of equipment to functional knee evaluation. For this, we used the product development methodology proposed by Bach et al. (2008) until the creation of the equipment prototype. The prototype consisted of a pedal moved at a speed and scale programmable by a stepper motor. In the distal portion of the pedal, there is a coupled dynamometer that checks the force applied during the execution of the flexion and extension movements of the knee. The evaluator has a computer that programs the speed and the angular position of the pedal, as well as, gets the information from the dynamometer. After the construction of the prototype, it was verified that the development of the proposed equipment is feasible and cost effective. Therefore, it is suggested the improvement of the prototype for the construction of the final product.